2006
DOI: 10.1104/pp.106.082743
|View full text |Cite
|
Sign up to set email alerts
|

Trichomes of Tobacco Excrete Zinc as Zinc-Substituted Calcium Carbonate and Other Zinc-Containing Compounds

Abstract: (S.F., M.A.M.) Tobacco (Nicotiana tabacum L. cv Xanthi) plants were exposed to toxic levels of zinc (Zn). Zn exposure resulted in toxicity signs in plants, and these damages were partly reduced by a calcium (Ca) supplement. Confocal imaging of intracellular Zn using Zinquin showed that Zn was preferentially accumulated in trichomes. Exposure to Zn and Zn 1 Ca increased the trichome density and induced the production of Ca/Zn mineral grains on the head cells of trichomes. These grains were aggregates of subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 49 publications
3
80
2
1
Order By: Relevance
“…Calcium oxalate mono and 34 dihydrate were found occasionally. Calcite and vaterite were substituted by cations, probably Zn, 35 Cd and possibly Mn and Mg. Zn µEXAFS confirmed the occurrence of Zn-substituted calcite, 36 and evidenced Zn associations with other phases including organic compounds, silica and 37 phosphate (3). Cd µXANES showed that cadmium was a Ca substituent in calcite and vaterite 38 and/or sorbed on the surface of these minerals (Isaure et al, in prep.).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Calcium oxalate mono and 34 dihydrate were found occasionally. Calcite and vaterite were substituted by cations, probably Zn, 35 Cd and possibly Mn and Mg. Zn µEXAFS confirmed the occurrence of Zn-substituted calcite, 36 and evidenced Zn associations with other phases including organic compounds, silica and 37 phosphate (3). Cd µXANES showed that cadmium was a Ca substituent in calcite and vaterite 38 and/or sorbed on the surface of these minerals (Isaure et al, in prep.).…”
mentioning
confidence: 70%
“…Xanthi). Tobacco exposed to Cd excreted Cd,Ca-containing grains 21 through leaf trichomes (1,2), and a similar excretion of Zn,Ca-containing grains was observed 22 under Zn exposure (3). Trichomes are specialized epidermal structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As both biogenic and non-biogenic crystals have been shown to serve as hosts for organic molecules 1, 2 and for metal ions, their interaction has been extensively studied. In particular, calcium-bearing minerals that plant organisms produce, [3][4][5][6][7][8][9][10] as well as calcium carbonate and hydroxyapatite, [11][12][13][14] have been shown to absorb or exchange foreign cations effectively. [14][15][16] A variety of cations have been tested for their sorption behavior especially on calcium carbonate and hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, oxalic acid accumulated at higher levels in ANR plants in a pattern similar to that of the cembranoids. Oxalate, which accumulates in glandular trichomes and idioblast cells of Nicotiana species (Choi et al 2001;Sarret et al 2006;VolkA and Franceschi 2000), is the calcium salt of oxalic acid and has important defensive activities against chewing insects (Korth et al 2006). We microscopically examined trichomes, but did not observe changes of their morphology and density on the surfaces of stems and leaves between transgenic and WT tobacco plants (Fig.…”
Section: Impacts Of Anr Transgene On Metabolic Profilesmentioning
confidence: 99%